Greenmaize potential of hybrid and openpollinated cultivars at varying levels of applied nitrogen: relationship with grain yield - Kim, S.K.; Adetimirin, Victor O.; Yoon, S.T.; Adepoju, A.; Gbadamosi, B.A. (Wiley, 2007)
Two sets (white- and yellow-kernelled) of six cultivars of field-maize, each comprising three hybrids and three open-pollinated (OP) varieties, were evaluated for green-maize productivity under three levels of nitrogen fertilisation (0, 60 and 120 kg ha−1) at two locations in southwestern Nigeria. The relationship between green-maize and grain yield was also investigated. Numbers of marketable ears and marketable-ear yield were significantly correlated. Green-maize traits and grain yields showed different responses to increased nitrogen fertiliser application: grain yield was significantly greater at 120 kg ha−1 than at 60 kg ha−1 whereas marketable-ear yield was not significantly changed by the higher rate. The hybrids showed higher green-maize and grain yield responses than the OPs to fertiliser application. At 60 kg ha−1 nitrogen application, marketable-ear yield averaged 0.620 kg m−2 and 0.567 kg m−2 for white hybrids and OPs, respectively, and 0.576 kg m−2 and 0.439 kg m−2 for yellow hybrids and OPs. Marketable-ear yield was significantly correlated with grain yield for both the white and yellow cultivars. Regressions of grain yield on marketable-ear yield were significant and such regression equations can thus be used to estimate marketable-ear yield potential from grain yield data.